Successful library fundraising : best practices - Wood, M. Sandra (Rowman and Littlefield, 2014)
Obtaining funding to maintain and grow library services and resources has always been a challenge. Successful Library Fundraising: Best Practices brings together a wealth of information from public, academic, special, and school libraries who share their successful approaches to raising funds through traditional and non-traditional methods.